Pengaruh Permainan Sticky Board Terhadap Kemampuan Literasi Awal Anak Kelompok A - Rapi, Us. Djuko; Waode Eti Hardiyanti; Nur Anisa Abdul Wahab (Student Journal of Early Childhood Education, 2023)
This study aims to determine the influence of the Sticky Board game on the early literacy skills of Group A children at said Kindergarten in the research site. It applied a quantitative pre-experimental design with a one-group pretest-posttest design. The findings revealed a difference in the average scores between the pretest and posttest, based on a sample of 26 children. The pretest data showed an average value of 15.1 and a standard deviation of 3.04, while the posttest data showed an average value of 32.5 and a standard deviation of 2.26. The findings demonstrated a significant influence before and after the implementation. Based on the output of the Statistical Test, the T count value was 17.7, and the T table value was 2.048. Thus, the value was 17.7> 2.048, and the hypothesis is accepted. Therefore, the research hypothesis stated that there is an influence of the Sticky Board Game on the Early Literacy Skills of Group A Children at TK Mekar Wangi Kindergarten in Botubarani Village, Kabila Bone District, Bone Bolango Regency.